A secure transaction environment for workflows in distributed systems - Wietrzyk, V.I.; Takizawa, M.; Orgun, M.A.; Varadharajan, V. (Proceedings. Eighth International Conference on Parallel and Distributed Systems. ICPADS 2001, 2001)
The paper describes the design of a model as well as an architecture to provide support for distributed advanced workflow transactions. We discuss the application of transaction concepts to activities that involve integrated execution of multiple tasks over different processes. This kind of application is described as transactional workflow. The classical commit protocol, used in many commercial systems, is not suitable for use in multilevel secure distributed workflow database systems that use a locking protocol for concurrency control. The reason is that it is not possible for a locking protocol to guarantee that read locks won't be released by a subtransaction during its window of uncertainty-the period after a participant has voted yes to commit, but before it receives the commit or abort decision from the coordinator, possibly resulting in nonserializable executions. A distinguishing feature of the proposed workflow transaction support system is the ability to manage the arbitrary distribution of business processes over multiple workflow management systems.